‘The Oceans are Rising and So Are We’: Exploring Utopian Discourses in the School Strike For Climate Movement - Heather McKnght (Janeway JS, 2020)
This article presents some provisional analysis of discourses presented by school students under the banner of the movements: Fridays for Future, Youth for Climate and School Strike 4 Climate. It contends that these movements go beyond just presenting a vision of an inescapable future, or a simplistic request for adults to listen to science. Instead, their vision is constructive of a better world as they challenge the failures of politicians, and arguably the adult public, demanding to play an active role in policy making when it comes to climate crisis. The article argues that this movement is constructed of a critical utopian discourse expressed through complex temporalities, which define the role of resistance as anticipation. It considers how the anxiety in the Student Strike movement creates a militant optimism, and the narratives of cathedral thinking are demonstrative of an open-ended utopian process.
Keywords: VÄlmÄ«ki RÄmÄyaá¹‡a; BrahmapurÄá¹‡a; SÄmajÄtaka; DaÅ›aratha